Synergistic use of sodium bicarbonate and aluminum sulfate to enhance the hydration and hardening properties of Portland cement paste. (13th September 2021) - Liu, Songhui; Shen, Yuanyuan; Wang, Yuli; He, Hang; Luo, Shuqiong; Huang, Cunhan
Highlights: The work provides a novel and facile method for the generation of in situ CaCO3 in cement paste. The N-A admixture significantly increases the early strength of Portland cement. The N-A admixture promotes the formation of AFt and CaCO3 . The in situ CaCO3 can react with the aluminum phase to form mono-carbonate (Mc). Abstract: A novel composite admixture (N-A admixture) including sodium bicarbonate (NaHCO3 ) and aluminum sulfate (Al2 (SO4 )3 ) was developed for the in situ generations of calcium carbonate (CaCO3 ) nano-reinforced particles in Portland cement paste. The effect of N-A admixture dosage (0%, 1%, 2%, 3%, 4%, 5%) on the hydration and hardening properties of Portland cement paste such as setting time and compressive strength was systematically investigated. The enhancement mechanism of the N-A admixture was also revealed by using XRD, TGA, SEM, MIP, and ICC. The results indicated that the N-A admixture can effectively accelerate the hydration reaction process of Portland cement paste and shorten its setting time. When the N-A admixture was added at 3%, the compressive strength at 1 day was 86.9% higher than that of the control Portland cement paste, and there was no inversion of strength at 90 days. N-A admixture promoted the formation of more hydration products. At the early stage of hydration, in situ CaCO3 with a grain size ranging from 25.53 to 42.98 nm was generated, the amount of which increased with the addition of N-A admixture. Moreover, the in situ CaCO3 also reacted with the aluminum phase to form mono-carbonate (Mc) in the late stage, which effectively reduced the proportion of large pores, resulting in a dense microstructure of the hardened Portland cement paste. The results of this work provide a novel and facile method for the generation of in situ CaCO3, which can be used to greatly improve the performance of cement concrete.